Analysis of the Effect of Marketing Mix on Customer Satisfaction: Case Study at Ikan Bakar Bekre Le Ewok Restaurant in Bandar Lampung - Diki Firnando; Dora Rinova; Niki Agus Santoso (Eastasouth Institute, 2026)
This study examines the effect of the marketing mix, consisting of product, price, place, and promotion, on customer satisfaction at Ikan Bakar Bekre Le Ewok Restaurant in Bandar Lampung. A quantitative research design was employed using a survey method. Data were collected from 150 customers through accidental sampling and analyzed using multiple linear regression. Prior to hypothesis testing, validity and reliability tests were conducted to ensure the quality of the research instrument. The results indicate that product, price, place, and promotion have a positive and significant effect on customer satisfaction (p < 0.05). Simultaneously, all marketing mix variables were found to significantly influence customer satisfaction. Among the variables examined, price emerged as the most dominant factor, followed by promotion, place, and product. The coefficient of determination (R² = 0.682) shows that 68.2% of customer satisfaction can be explained by the marketing mix variables, while the remaining 31.8% is influenced by other factors outside the scope of this study. These findings highlight the importance of effective marketing mix management in improving customer satisfaction. Therefore, restaurant management should focus on maintaining competitive pricing, strengthening promotional activities, improving location-related facilities and convenience, and ensuring consistent product quality to enhance customer satisfaction and business competitiveness.